Jakość usług ubezpieczeniowych - ukryte wymiary w świetle analizy czynnikowej - Garczarczyk, Józef; Mocek, Marek (The Quality of Insurance Services - Hidden Dimensions in the Light of Factor Analysis, 2006)
The problem of service quality management in insurance companies has presently become the leading issue on the increasingly competitive Polish financial market. The quality of services and the resulting customers' satisfaction and loyalty are the basic factors allowing for the achievement of the competitive edge. However, as far as now, comprehensive theoretical and practical knowledge as well as the full knowledge of the mechanisms of optimal quality management in insurance companies is deficient. In order to build a quality control system, profound knowledge of the clients' preferences, expectations and requirements concerning the quality of insurance services is necessary. The quality must be adjusted to the needs of particular segments of buyers. Therefore, the results of three national surveys which were conducted especially for this purpose served as the source basis for the implementation of this aim. 982 households, 631 companies from various sectors of economy and 270 insurance companies' managers participated in the surveys. All the surveys used the same measure method to assess 32 isolated factors of insurance service quality - a five point Likert scale, allowing for the full comparability of the results achieved. The quality components were being assessed at all four stages of the development of quality-ensuring system in an insurance company - i.e. at the identification of quality attributes stage, system preparation stage, system implementation stage as well as at the final assessment of the quality of the insurance company's services stage. The use of exploratory factor analysis in editing the empirical material collected in the surveys allowed for the identification of the hidden factors of the quality of insurance services. The reduction of variables achieved in this way helped also to simplify the description of the quality management system in insurance companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 334-351